Adult Age Differences in Effects of Text Spacing on Eye Movements During Reading - Li, Sha; Oliver-Mighten, Laurien; Li, Lin; White, Sarah J.; Paterson, Kevin B.; Wang, Jingxin; Warrington, Kayleigh L.; McGowan, Victoria A. (Frontiers in Psychology, 2019)
Large-scale changes in text spacing, such as removing the spaces between words, disrupt reading more for older (65+ years) than younger (18–30 years) adults. However, it is unknown whether older readers show greater sensitivity to simultaneous subtle changes in inter-letter and inter-word spacing encountered in everyday reading. To investigate this, we recorded young and older adults’ eye movements while reading sentences in which inter-letter and inter-word spacing was normal, condensed (10 and 20% smaller than normal), or expanded (10 or 20% larger than normal). Each sentence included either a high or low frequency target word, matched for length and contextual predictability. Condensing but not expanding text spacing disrupted reading more for the older adults. Moreover, word frequency effects (the reading time cost for low compared to high frequency words) were larger for the older adults, consistent with aging effects on lexical processing in previous research. However, this age difference in the word frequency effect did not vary across spacing conditions, suggesting spacing did not further disrupt older readers’ lexical processing. We conclude that visual rather than lexical processing is disrupted more for older readers when text spacing is condensed and discuss this finding in relation to common age-related visual deficits.